The Cybersecurity Guide to Governance, Risk, and Compliance - Edwards, Jason; Weaver, Griffin (Hoboken, New Jersey John Wiley & Sons, 2024)
"Cyber Security Governance & Risk Management is the monitoring of compliance with agreed cyber security policies and the assessment and management of relevant risks. Cybersecurity is a critical concern for modern businesses, and understanding how to navigate it is vital"-- Provided by publisher.
CHAPTER 1 : Governance, Risk Management, and Compliance -- CHAPER 2 : The Landscape of Cybersecurity -- CHAPTER 3 : Cybersecurity Leadership: Insights and Best Practices -- CHAPTER 4 : Cybersecurity Program and Project Management -- CHAPTER 5 : Cybersecurity for Business Executives -- CHAPTER 6 : Cybersecurity and the Board of Directors -- CHAPTER 7 : Risk Management -- CHAPTER 8 : The NIST Risk Management Framework -- CHAPTER 9 : Cybersecurity Metrics -- CHAPTER 10 : Risk Assessments -- CHAPTER 11 : NIST Cybersecurity Framework -- CHAPTER 12 : Cybersecurity Frameworks -- CHAPTER 13 : NIST SP 800-53: Security and Privacy Controls Framework – CHAPTER 14 : The FFIEC : An Introduction -- CHAPTER 15 : U.S. Federal Cybersecurity Regulations -- CHAPTER 16 : State-level Cybersecurity Regulations -- CHAPTER 17 : International Cybersecurity Laws and Regulations -- CHAPTER 18 : Privacy Laws and Their Intersection with Cybersecurity -- CHAPTER 19 : Auditing Cybersecurity: Guides for Auditors and the Audited -- CHAPTER 20 : The Challenging Role of the Regulator -- CHAPTER 21 : Understanding US Regulatory Bodies -- CHAPTER 22 : Managing Regulatory Visits and Requests for Information -- CHAPTER 23 : Understanding Regulatory Penalties -- CHAPTER 24 : Addressing and Remediating Regulatory Findings -- CHAPTER 25 : Cybersecurity Architecture -- CHAPTER 26 : Risk Mitigation -- CHAPTER 27 : Cloud Security -- CHAPTER 28 : Artificial Intelligence in Cybersecurity -- CHAPTER 29 : Quantum Computing: A New Frontier -- CHAPTER 30 : Incident Response and Recovery - CHAPTER 31 : Navigating the Cyber Insurance Maze.
Includes index
Keywords: Business enterprises -- Computer networks -- Security measures; Computer security